Dampak Revitalisasi Objek Wisata Embung Cerme Melalui Budidaya Tanaman Buah: Impact of Revitalizing the Tourism Attraction of Embung Cerme Through Fruit Plant Cultivation - Haurelia, Nathania Fredlina Shaffa; Wibowo, Agung; Padmaningrum, Dwiningtyas (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
Embung Cerme is a tourist attraction in Sanggang Village, Bulu District, Sukoharjo Regency, Central Java. In 2012, the Cerme Embung was built as a facility to store rainwater and irrigate plants. This reservoir was abandoned in 2013 due to a lack of structured management and limited development funds. Until 2018, Embung Cerme was revived through a revitalization process and became a new tourist attraction. Embung Cerme's revitalization mechanism consists of physical intervention, social intervention, economic intervention and environmental intervention. The impact of revitalization influences society from economic, socio-cultural and ecological aspects. The aim of the study was to determine the impact of the revitalization that took place in Embung Cerme through the cultivation of fruit plants. This research uses a qualitative analysis method with a descriptive approach with data sources of in-depth interviews, observation and documentation. As a result, the revitalization of Embung Cerme has had positive and negative consequences in every aspect. The positive impact is felt more by the people of Sanggang Village. This shows that the revitalization of Embung Cerme through the cultivation of fruit plants has been successful and can be sustainable. Keywords : Cultivation, Empowerment, Impact, Reservoir, Revitalization